(untitled) (Medical Forum Monthly, 2024)
Objectives: To determine the frequency of subclinical hypothyroidism in patients with proliferative diabetic retinopathy. Study Design: Cross Sectional Study. Place and duration of study: This study was conducted in Dow University Hospital, Dow University of Health Sciences , Karachi from 1st January 2012 to 31st December 2012. Materials and Methods: One hundred and nineteen patients attending the medicalOPD Dow University of Health Sciences were included in study. Results: 119 patients were enrolled in study .47.1% were male and 52.9% were female patients mean age was 55.75±7.85 years , Mean HbA1c value was 8.02 ± 1.46%,Subclinical hypothyroidism was identified in 26.9% the patients. Conclusion: Subclinical hypothyroidism is associated with the development of proliferative diabetic retinopathy in the patients suffering from type 2 diabetics.